Digital Jihad in Qur’anic Perspective: An Islamic Response to the Challenges of Cyberspace in the Age of Artificial Intelligence (AI) - Hamka Ilyas; Abd. Bashir Fatmal; La Ode Ismail Ahmad (QOF, 2025)
This study examines the concept of digital jihad from a Qur’anic perspective as a normative, ethical, and strategic response to the complex challenges of cyberspace in the era of Artificial Intelligence (AI). The research is motivated by the growing integration of digital technology in religious life, alongside the proliferation of disinformation, algorithmic manipulation, and AI-enabled simulations of religious authority. Employing a thematic interpretation approach (tafsīr mawḍū’ī), the study analyzes Qur’anic verses, particularly QS. al-Hajj [22]:78 and QS. al-Furqan [25]:52, which emphasize nonviolent jihad rooted in knowledge (‘ilm), argumentation (ḥujjah), and Qur’anic ethics. The findings indicate that digital jihad is a multidimensional effort encompassing educative da’wah, resistance to digital radicalism, counter-narratives against extremism, and the ethical deployment of AI. It also entails proactive engagement in fostering a digital Islamic civilization grounded in moderation (wasatiyyah), truth verification (tabayyun), and moral responsibility. The primary contribution of this study lies in conceptualizing digital jihad as a transformative, adaptive tool for da’wah that enables Muslims to ethically navigate and shape digital spaces within a value-based framework. This research thus expands the discourse on jihad beyond militaristic interpretations, offering a contemporary Qur’anic paradigm that is both intellectually rigorous and practically relevant to today’s socio-technological realities